ASPEK RELIGIOSITAS DALAM DUA NOVEL ERICÂEMMANUEL SCHMITT: MONSIEUR IBRAHIM AND THE FLOWERS OF THE KORAN DAN OSCAR AND THE LADY IN PINK - Saraswati, Rina (ATAVISME, 2012)
Tema religiositas merupakan sesuatu yang lazim muncul dalam karya sastra, mengngat kedekatannya dengan masalah filsafat. Bersikap religius intinya adalah berserah diri pada kekuatan yang lebih besar untuk mencapai kebahagiaan yang sifatnya pribadi. Berbicara mengenai religiositas tidak selalu harus dikaitkan dengan agama tertentu. Namun, melalui nilainilai yang diajarkan masingmasing agama akan terefleksikan nilainilai kemanusiaan yang universal yakni cinta, kasih sayang, dan misteri hidup. Aspek religiositas yang universal itulah yang dijadikan inti pembahasan tulisan ini melalui kajian interteks dua karya EricEmmanuel Schmitt: Monsieur Ibrahim and the Flowers of the Koran dan Oscar and the Lady in Pink. Abstract: The theme of religiosity is something that commonly appears in literature, given its proximity to the problems of philosophy. Being religious is essentially surrender to a greater power to achieve happiness which is private in nature. To speak about religiosity is not necessarily associated with any particular religion. But through the values that are taught in each religion, the values of humanity, that is universal love, compassion, and the mystery of life, will be reflected. It is the universal aspect of religiosity that will be the core of the discussion of this paper through intertextual study of two works of EricEmmanuel Schmitt: Monsieur Ibrahim and the Flowers of the Koran and Oscar and the Lady in Pink. Key Words: religiosity, religion, happiness, mystery, intertextual